STRATEGIC MANAGEMENT OF COMMUNITY-BASED EDUCATION ORGANIZATIONS IN RURAL PAPUA A CASE STUDY OF YAYASAN HANO WENE INDONESIA - Neas Wanimbo; Awang Darmawan Putra; Anandha Budiantoro (Journal of Management and Leadership, 2026)
Abstract Education remains a major challenge in rural Papua due to geographical barriers, limited educational infrastructure, shortages of qualified teachers, and the lack of culturally relevant educational approaches for indigenous communities. Community-based education organizations have emerged as important actors in addressing these challenges and expanding educational access in remote areas. Despite the growing body of literature on strategic management, existing studies have predominantly focused on business organizations, urban non-governmental organizations, and formal educational institutions, while limited attention has been given to community-based education organizations operating within indigenous contexts in rural Papua. This study aims to analyze the strategic management practices of Yayasan Hano Wene Indonesia, a community-based education organization serving indigenous communities in rural Papua. The study employs a qualitative case study approach using interviews, observations, documentation, and literature review as data collection methods. Resource-Based Theory (RBT) and the VRIO Framework are applied to identify and evaluate the organization’s strategic resources. The findings reveal that the organization’s primary strengths are derived from intangible resources, including community trust, cultural knowledge, social networks, field experience, and volunteer commitment. The VRIO analysis demonstrates that community trust, local cultural understanding, and strong social relationships constitute sustainable strategic advantages because they are valuable, rare, difficult to imitate, and effectively organized within the institution. The findings also highlight the significant influence of indigenous Papuan cultural contexts on organizational strategy and decision-making processes. This study contributes to the strategic management literature by extending the application of Resource-Based Theory and the VRIO Framework to community-based education organizations operating in indigenous settings. Practically, the findings provide insights for community organizations, policymakers, and educational stakeholders seeking to strengthen sustainable and culturally responsive education initiatives in rural and indigenous communities. Keywords: Strategic Management, Community-Based Education, Resource-Based Theory, VRIO Framework, Indigenous Education, Papua